Accuracy and Injection Force of the Gla-300 Injection Device Compared With Other Commercialized Disposable Insulin Pens. (January 2016) - Klonoff, David; Nayberg, Irina; Thonius, Marissa; See, Florian; Abdel-Tawab, Mona; Erbstein, Frank; Haak, Thomas
Background: To deliver insulin glargine 300 U/mL (Gla-300), the widely used SoloSTAR ® pen has been modified to allow for accurate and precise delivery of required insulin units in one-third of the volume compared with insulin glargine 100 U/mL, while improving usability. Here we compare the accuracy and injection force of 3 disposable insulin pens: Gla-300 SoloSTAR ®, FlexPen ®, and KwikPen™. Methods: For the accuracy assessment, 60 of each of the 3 tested devices were used for the delivery of 3 different doses (1 U, half-maximal dose, and maximal dose), which were measured gravimetrically. For the injection force assessment, 20 pens of each of the 3 types were tested twice at half-maximal and once at maximal dose, at an injection speed of 6 U/s. Results: All tested pens met the International Organization for Standardization (ISO) requirements for dosing accuracy, with Gla-300 SoloSTAR showing the lowest between-dose variation (greatest reproducibility) at all dose levels. Mean injection force was significantly lower for Gla-300 SoloSTAR than for the other 2 pens at both half maximal and maximal doses ( P < .0271). Conclusion: All tested pens were accurate according to ISO criteria, and the Gla-300 SoloSTAR pen displayed the greatest reproducibility and lowest injection force of any of the 3 tested devices.